The integration of information technology skills in accounting curriculum at public universities in Egypt - Ayman Mohamed Sabry Shaban Nokhal (2013)
Professional and academic accountants have debated the issue of integration of information technology (IT) skills in accounting during the past three decades. However, the majority of prior studies are very descriptive in nature and lack a theoretical background. Most of these studies investigated the issue separately, either from the perspective of professional or academic accountants. Based on information processing theory and task-technology fit, this study investigates the alignment (IT Alignment)between Required IT skills and Integrated IT skills in single setting. It also examined factors that influence IT Alignment. Data were collected from 249 accounting lectures in public universities in Egypt, who were also practicing accountants. Survey was mailed out in March 2011, and response rate was 69.02%. Descriptive statistics indicated that the top 5 Required IT were generalized audit software, embedded audit modules/real-time modules, word processing, small business accounting software, and electronic spreadsheets, electronic presentations, database search and retrieval, and test data. Using a matching approach, the top 5 most aligned variables were word-processing, electronic spreadsheets, electronic presentations, internal network configurations, and database search and retrieval. Thirty-five hypotheses were then tested to examine factors that influenced IT Alignment. Results of multiple regressions suggested that market need played a major role in influencing the IT alignment. Other factors included financial resources, university/faculty support, interest and attitude toward the IT integration. This study has deepened current understanding of IT integration into accounting and has provided useful insights for Dean of Faculty of Accountancy in planning their IT integration. More importantly, the study also opens up possibilities for further study of IT integration, both in Egypt and around the globe.